PALYNOLOGICAL INVESTIGATION OF THE OLIGOCENE SEDIMENT IN EAST JAVA SEA - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2007)
The palynological study of the Oligocene sediments is based on cutting samples collected from the exploration wells which are drilled in East Java Sea. The occurrence of pollen Meyeripollis naharkotensis along the well sections suggests the pollen zone of Meyeripollis naharkotensis which is equivalent to Oligocene age. This is supported by the regular occurrence of the Oligocene marker of the trilete spore of Cicatricosisporites dorogensis along the studied well sections. In addition, foraminiferal and nannoplankton analyses confirm the Oligocene age by identifying the occurrence of letter stage of Tc- Te4 and nanno zone of NP21-NP25. On the other hand, most palynomorphs marking Eocene age disappear from the studied wells as they are stratigraphically older than the studied sediments. Unlike the Oligocene sediment of West Java and Central Sumatra which was formed in the freshwater swamp or lake under dry climate condition, the studied sediment was deposited in the transition to shallow marine environment as indicated by the moderate diversity of marine dinoflagellates coupled with the frequent occurrence of limestone along the sections. Furthermore, the regular appearance of back-mangrove pollen of Spinizonocolpites echinatus throughout the well sections supports the indication of marine influence. The appearance of the Australian immigrants including Dacrydium (common occurrence) and Casuarina (regular occurrence) may indicate earlier arrival of the Australian continent in this area compared to that in other areas of Indonesia.